2020
DOI: 10.1371/journal.pone.0237471
|View full text |Cite
|
Sign up to set email alerts
|

Diffusing science through social networks: The case of breastfeeding communication on Twitter

Abstract: Breastfeeding is one of many health practices known to support the survival and health of mother and infant, yet low breastfeeding rates persist globally. These rates may be influenced by limited diffusion of evidence-based research and guidelines from the scientific community (SC). As recently highlighted by the National Academy of Sciences, there is a need for the SC to diffuse its findings to the public more effectively online, as means to counteract the spread of misinformation. In response to this call, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
(42 reference statements)
1
19
0
Order By: Relevance
“…The proposition that the virtual world can be socially mapped and measured to provide insights and action is a quickly evolving space [39,40]. Precedents of effective SNT-based applications for online data have been set, predominately in the field of education and policy and, more recently, in public health [19][20][21]39]. An ample amount of data from these studies suggests social media is the "backbone" of the Internet, where all types of media, links, ideas, opinions, and tools are shared among social networks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The proposition that the virtual world can be socially mapped and measured to provide insights and action is a quickly evolving space [39,40]. Precedents of effective SNT-based applications for online data have been set, predominately in the field of education and policy and, more recently, in public health [19][20][21]39]. An ample amount of data from these studies suggests social media is the "backbone" of the Internet, where all types of media, links, ideas, opinions, and tools are shared among social networks.…”
Section: Discussionmentioning
confidence: 99%
“…We used the same data collection approach during the six months prior to the campaign to capture all tweets and associated user data that included breastfeeding-related hashtags (Table 1). These specific hashtags were chosen based on our previous research that identified commonly-used hashtags in this space [19][20][21]. With no previous data available from last year's campaign, we chose a sixmonth period as a conservative period to prevent covering tweets related to the previous year's campaign.…”
Section: A) Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Social media influencers have recently been highlighted for their potential to reach audiences in a credible, relatable way that is outside the scope of traditional on-the-ground or digital campaigns (Djafarova et al 2017 ; Freberg et al 2011 ). Research has shown their potential utility in promoting reproductive health-related behaviors such as breastfeeding or HPV vaccination (Moukarzel et al 2020 ; Ortiz et al 2019 ). Influencers were identified manually, by searching local hashtags and business for accounts that appeared influential or attracted engagement from others.…”
Section: Methodsmentioning
confidence: 99%